2013
DOI: 10.1111/gfs.12037
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of mixing grasses and legumes for herbage yield and nutritive value inNorthernEurope andCanada

Abstract: Increased biodiversity may improve ecosystem services, including herbage yield. A mixture experiment was carried out at five sites in Northern Europe and one in Canada to investigate whether mixtures of grasses and legumes would give higher herbage yield than monocultures. Resistance of the mixtures to weed invasion and nutritive value of the herbage were also investigated. The experimental layout followed a simplex design, where four species differing in specific functional traits, timothy (Phleum pratense L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 53 publications
15
106
1
Order By: Relevance
“…In the current study, greater TDM was measured in the L cuneata legume plot whereas the lowest TDM yield was recorded in the control plot. This finding is in agreement with the study of (Sturludottir et al [17]) that was conducted in Northern Europe and Canada which, reported higher yield in the legume-grass mixtures than monoculture treatments. The authors reported that on average, the legume-grass mixture plots had 9%, 15% and 7% more DMY than the most productive monoculture in the first, second and third year respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, greater TDM was measured in the L cuneata legume plot whereas the lowest TDM yield was recorded in the control plot. This finding is in agreement with the study of (Sturludottir et al [17]) that was conducted in Northern Europe and Canada which, reported higher yield in the legume-grass mixtures than monoculture treatments. The authors reported that on average, the legume-grass mixture plots had 9%, 15% and 7% more DMY than the most productive monoculture in the first, second and third year respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has established that the species composition of mixtures is more important than the richness (Deak et al, 2007;Sanderson, 2010) or evenness (Sturludóttir et al, 2013) of species in affecting forage nutritive value. In this research, we determined the additive effect of individual grass or legume species in a mixture on forage nutritive value, or the expected change in nutritive value of a mixture as the contribution of a particular species increases from 0 to 100% of the mixture on a compositional basis.…”
Section: Researchmentioning
confidence: 99%
“…Results of a pan-European experiment, which included a Canadian site, have demonstrated that mixing grasses and legumes increases dry matter (DM) yield (Finn et al 2013) with no negative effects on nutritive value (Sturludóttir et al 2013). Adding a legume into a grass sward has been shown to increase forage DM yield and crude protein concentration (Barnett and Posler 1983) and improve forage nutritive value (Papadopoulos et al 2001).…”
Section: Introductionmentioning
confidence: 99%